2023
DOI: 10.3346/jkms.2023.38.e326
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Vaccination: A Narrative Review

Flinta Rodrigues,
Nelly Ziade,
Kanon Jatuworapruk
et al.

Abstract: Vaccine hesitancy poses a significant global health challenge, fueled by misinformation and anti-vaccination campaigns on social media platforms (SMPs). This study examines the influence of social media on coronavirus disease 2019 (COVID-19) and non-COVID-19 vaccination in Asia during the peri-pandemic period. Through a comprehensive analysis of available literature, we aim to elucidate the role of SMPs in shaping vaccination attitudes and behaviors. The findings highlight the detrimental impact of social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…A hyper-connected population has turned social networks into fertile ground for spreading false information about vaccines, the COVID-19 pandemic, its treatment options, and other "instant miracle cures." This proliferation has severely compromised opinions about vaccine efficacy and trust in health authorities [40]. This dynamic is exacerbated by the speed and reach of digital platforms, where people can become confused and distrustful of each other as incorrect information spreads rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…A hyper-connected population has turned social networks into fertile ground for spreading false information about vaccines, the COVID-19 pandemic, its treatment options, and other "instant miracle cures." This proliferation has severely compromised opinions about vaccine efficacy and trust in health authorities [40]. This dynamic is exacerbated by the speed and reach of digital platforms, where people can become confused and distrustful of each other as incorrect information spreads rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a large proportion of our study subjects (more in the US cohort than in the Lebanese cohort) obtained their health information from social media. In a recent narrative review, COVID-19 vaccine hesitancy correlated positively with reliance on social media as a source of information [ 22 ]. Given its powerful influence, it is therefore important to use social media as a means of disseminating reliable scientific information in lieu of its use to propagate conspiracy theories.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown that using social media as a source of vaccine information without any other trusted source was associated with vaccine hesitancy [ 1 , 40 , 47 ]. A meta-analysis conducted on vaccine hesitancy showed that there had been a distinct rise in the phenomenon since COVID-19, with a 293% increase in articles published concerning vaccine hesitancy from the pre-COVID to post-COVID period, emphasizing the gravity of this issue and the necessity for public health measures to combat this phenomenon [ 22 ].…”
Section: Discussionmentioning
confidence: 99%